Critical perspectives on the Motor Industry Development Programme as a post-apartheid industrial policy instrument - Nkunzi, Sibulele (My University, 2015)
The South African automotive industry, which for a long period was inward-looking and isolated from the global environment, is now fully integrated into the global automotive industry. Between 1995 and 2012, the government subsidised the South African automotive industry with the aim of building its global competitiveness through the Motor Industry Development Programme (MIDP). The Purpose of this study was to critically evaluate the MIDP as an industrial policy instrument to enhance the global competiveness of the South African automotive industry. A knowledge base in the form of a theoretical framework was created, focusing on the neoclassical vis-à-vis the structuralist understanding of industrial policy and the role of the state in development. This was followed by a literature review which problematized the industrial and economic policies that have shaped the path of industrialisation in South Africa, as well as their subtle influences on the automotive industry policy. An overview of the MIDP and its instruments as well as the critical evaluation of the performance of MIDP against its objectives was done. The study shows the results have been particularly disappointing with respect to employment, the development of domestic supplier industries and the attraction of manufacturing capabilities and competencies linked to learning. The findings suggest that limitations of government enforcement of reciprocal control mechanisms (RCMs) on original equipment manufacturers (OEMs); the state-labour-industry institutional arrangements in the policy process; as well as the subtle influences of neoliberal policies and weak governmental capacities at the Department of Trade and Industry, explain the disappointing results of the MIDP.
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2014.